Practice of Islamic Philanthropy in Indonesia - Djalil, Noviendri (ZISWAF, 2026)
The purpose of this study is to find out about Islamic philanthropic activities in Indonesia to increase knowledge and learning in the development of Islamic philanthropy. The research method used in this study is a library study and literature on readings and research results published in previous journals which are then analyzed and summarized how to collect, utilize and impact philanthropy on society. Philanthropy in Indonesia is managed by government and non-government institutions in the form of services in the form of collection, management and utilization or empowerment for the welfare of society. The impacts caused by Islamic philanthropy in Indonesia include economic empowerment, education, health, and humanity. This study is expected to help practitioners of Islamic philanthropy in Indonesia and the Islamic world in knowing and understanding the practice of collecting, managing and utilizing or empowering funds collected by philanthropic institutions in Indonesia for the welfare of society. This study is also intended to be a recommendation in efforts to improve and function Islamic philanthropic institutions in Indonesia to improve the welfare of society